The relationship between the individual biomechanical properties of the eye and the intraocular pressure measurements based on modern methods of ocular tonometry - M.D. Kats (РМЖ "Клиническая офтальмология")
M.D. Kats1,2 1O.M. Filatov City Clinical Hospital No. 15, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation A thorough analysis of the intraocular pressure (IOP) measurements is crucial for making diagnosis and decisions concerning the management of glaucoma patients. At the same time, there is a large inter-individual variability of ocular anatomical and physiological parameters impacting such measurements. IOP has been identified as a potential independent risk factor for the glaucoma progression. However, in clinical practice it is not always possible to achieve its accurate quantitative evaluation. Currently, multiple modern devices are available to determine IOP indicators and biomechanical properties of the eye. In addition, various clinical algorithms have been proposed for adjusting these indicators and thus to ensure an adequate interpretation of IOP measurements. However, there are still no clear guidelines on how to use the correction factors. In turn, the interpretation of measurement results with consideration of new (biomechanical) characteristics of the eye's support structure, requires a detailed analysis of the received data to establish correlations between non-standard parameters and specific characteristics of the glaucoma progression. This review presents an assessment of the latest ophthalmotonometry methods and their individual characteristics based on the available clinical experience. Keywords: ophthalmotonometry, biomechanical properties of the eye, intraocular pressure, glaucoma. For citation: Kats M.D. The relationship between the individual biomechanical properties of the eye and the intraocular pressure measurements based on modern methods of ocular tonometry. Russian Journal of Clinical Ophthalmology. 2023;23(2):86–93 (in Russ.). DOI: 10.32364/2311-7729-2023-23-2-86-93.